Co-expression Network Analysis Reveals Novel Genes Underlying Alzheimer’s Disease Pathogenesis - Hu, Rui-ting; Yu, Qian; Zhou, Shao-dan; Yin, Yi-xin; Hu, Rui-guang; Lu, Hai-peng; Hu, Bang-li (Frontiers in Aging Neuroscience, 2020)
Background The pathogenesis of Alzheimer’s disease (AD) remains to be elucidated. This study aimed to identify the hub genes in AD pathogenesis and determine their functions and pathways. Methods A co-expression network for an AD gene dataset with 401 samples was constructed, and the AD status-related genes were screened. The hub genes of the network were identified and validated by an independent cohort. The functional pathways of hub genes were analyzed. Results The co-expression network revealed a module that related to the AD status, and 101 status-related genes were screened from the trait-related module. Gene enrichment analysis indicated that these status-related genes are involved in synaptic processes and pathways. Four hub genes (ENO2, ELAVL4, SNAP91, and NEFM) were identified from the module, and these hub genes all participated in AD-related pathways, but the associations of each gene with clinical features were variable. An independent dataset confirmed the different expression of hub genes between AD and controls. Conclusions Four novel genes that associated with AD pathogenesis were identified and validated, which provided novel therapeutic targets for AD.